Sistem Informasi Advertising Pengelolaan Pemesanan Pada Cv Satria Promosindo Banyumas Untuk Meningkatkan Efficiency Dan Usability Berdasarkan Mc Call Triangle Of Quality - Zeffanya Syahril; Mayasari Sasmmito; Suyudi Suyudi (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2022)
CV Satria Promosindo Company established by Adhi Suprayogo since 2012 which operates in the field of advertising services. The services offered are in the form of e-mail, banners, business cards, brochures, stickers. For offerings and ordering advertising services, it is still conventional, namely marketing goes to customers or customers comes to marketing, and reports are still manual based on Microsoft Excel, especially in making reports, so all of this causes order reports to be inefficient and in making payment transactions the order is still done manually, namely the cutomer and admin holding a meeting at a predetermined place to make payments in cash, therefore the time required is quite long, so in time payment transactions are not used properly or are not useful.Therefore this company needs a system to overcome some of these problems. In the system there are 2 users, namely customer and admin. The information that will be loaded on the customer page is the profile page, order page, transaction history page, transaction print options page, and information page. Meanwhile, the admin page consists of a customer page, material type page, product page, order page, page, transaction history page, and report printing options page. . System development method used is the System Development Life Cycle with waterfall. Pengujian models to determine how much and about the benefits of the system is to test the hypothesis and test the benefits.